Analysis of the Strengths and Weaknesses of Paradiplomacy to Increase Regional Tourism Attractiveness - Fajrina, Siti; Srifauzi, Aulia (Jurnal Studi Ilmu Pemerintahan, 2024)
This study aims to assess the strengths and weaknesses of paradiplomacy in Aceh Province, particularly in the context of the tourism sector, with the aim of economic improvement through the utilization of Aceh's potential. This research employs a thorough literature study to gather relevant data and insights using a qualitative approach. This research aims to analyze the effectiveness of paradiplomacy in promoting Aceh's tourism, emphasizing its role in improving economic prospects through halal tourism. This study reveals that paradiplomacy is an essential instrument for Aceh Province in utilizing natural resources, primarily through the promotion of halal tourism. The Aceh government actively engages with the global community, positioning Aceh as a desirable destination in the halal tourism sector. In addition, this paper highlights the role of disaster diplomacy as an avenue to implement paradiplomacy in Aceh, utilizing tourism potential for economic gain. Although Aceh has significant untapped tourism potential, several challenges must be overcome to realize its full economic benefits. Infrastructure limitations limited human resources, and lack of promotion emerge as critical obstacles. This study underscores the importance of active government involvement, supported by the Law on Governing Aceh (UUPA), to address these challenges and maximize Aceh's strengths in the tourism sector.